Diazoniabicyclo-type poly (ionic liquid) cross-linked polybenzimidazole membrane with improved phosphoric acid retention for HT-PEMFCs. (26th June 2022) - Liu, Fengxiang; Ma, Shengnan; Wang, Shuang; Li, Jinsheng; Wang, Xiaodong; Yong, Zhipeng; Cui, Yinghe; Liang, Dan; Wang, Zhe
Abstract: Poly (ionic liquid)s with ion-pair aggregates are recognized as excellent modifier for high-temperature proton exchange membranes. Herein, a bulky ionic liquid, N-(4-chlorobutyl)-N'-(5-Pentenyl)-1, 4-diazoniabicyclo-[2.2.2]-octane bromide ([CPDOc]Br2 ), is synthesized and incorporated into polybenzimidazole (PBI) polymer as side groups. During the membrane fabrication, the cross-linked networks and poly(ionic liquid) are formed simultaneously through an in-situ free radical reaction. Finally, the anions are exchanged into H2 PO4 − with base-acid doped. As a result, the PBI-CPDOc30 membrane with low PA uptake (139%) exhibits the highest conductivity (0.121 S cm −1  at 170 °C), higher than that of PBI (0.083 S cm −1 ) with a PA uptake of 221%. Moreover, the PBI-CPDOc20 membrane exhibit a PA retention of up to 81% after the 400 h-test at 160 °C. Graphical abstract: Image 1 Highlights: Novel cross-linked membranes based on PBI and bulky diazoniabicyclo-type PIL were prepared. P[CPDOc] can act as cross-linker, but also promote proton transport. PBI-CPDOc30 has a proton conductivity of 0.121 S cm −1 at 170 °C with low PA uptake (139%). PBI-CPDOc exhibits enhanced PA retention (up to 81%) than that of PBI (73%).